Gentoo G140 confocal left cornea - Peter Hadden; Akilesh Gokul; Satya Amirapu; Ratish Kurian; Charles McGhee; Jie Zhang (2022)
Left corneal confocal micrographs obtained post mortem from gentoo penguin G140